Cerebrospinal fluid α-synuclein in the differential diagnosis of parkinsonian syndromes. (September 2014) - Heegaard, Niels HH; Tanassi, Julia T; Bech, Sara; Salvesen, Lisette; Jensen, Peter Lüttge; Montezinho, Liliana CP; Winge, Kristian
ABSTRACT: : Aim: To evaluate the diagnostic value of the level of α-synuclein, DJ-1, and Alzheimer's disease markers in the cerebrospinal fluid (CSF) in patients with parkinsonian syndromes.Materials & methods: We measured α-synuclein, DJ-1 and Alzheimer's disease markers by quantitative immunoassays in 122 CSF samples from patients with Parkinson's disease (PD; n = 38), dementia with Lewy bodies (n = 20), multiple-system atrophy (n = 18), progressive supranuclear palsy (n = 28), corticobasal degeneration (n = 7), unspecified atypical parkinsonian disorders (n = 5) and healthy controls (n = 6).Results: The level of α-synuclein was significantly decreased in CSF from PD patients. For the total tau/α-synuclein ratio, we obtained an area under the curve of 0.80 of the receiver operating characteristics curve for the PD diagnosis. With a cut-off of 1.33, the tau/α-synuclein ratio had 93% diagnostic specificity at 75% sensitivity for PD.Conclusion: CSF α-synuclein measurement may be useful in the differential diagnosis of PD versus other parkinsonian syndromes. CSF α-synuclein is found at low levels in the CSF and requires specifically adjusted assays to be measured.